VALUE CLARIFICATION TECHNIQUE IN ENHANCING FORGIVENESS - Khairul Bariyyah Arif; Julianne Kamilia Riza; Parid Rilo Pambudi (Abjadia, 2019)
The ability to forgive others is a condition in which a person is able to change the negative influence and solve dissonance and distress that accompany some life events into something constructive and pleasant. One technique that can be used to improve forgiveness is the Value Clarification Technique. The purpose of this study is to find out whether value clarification techniques are effective in increasing the ability to forgive others in MTs students. The research method used was experimental research with the type of One group pretest-posttest design. The research subjects were 8th grade MTs Al-Urwatul Wutsqo Jombang which were selected by purposive sampling technique. The instruments used were the Enright Forgiveness Inventory (EFI) attitude scale, and the training guide used as training material. Data is analyzed by analysts at Wilcoxon Matched Pairs Signed Ranks Test. Based on the results of the study it can be concluded that the value clarification technique is effective to increase the ability to forgive others in MTs students. The suggestions for this  research are: (1) To get maximum results in the application of value clarification techniques, the counselor is expected to pay more attention to the cultural factors possessed by the subject, (2) Further researchers are expected to further deepen the research topic on self forgiveness (self-forgiveness/intrapersonal forgiveness), which is also a matter that needs attention, in order to maximize character education activities.